Maturação da afinidade e seleção de novos fragmentos de anticorpos via Phage Display: considerações sobre uso de peptídeos miméticos ou células intactas - Bezerra, Marcus Rafael Lobo (2024)
Cancer is a group of diseases characterized by the malignant behavior of cells in the body, leading to metastasis. Leukemias and lymphomas are types of cancer originating from alterations in immune system cells. Antibodies are glycoproteins produced by B lymphocytes and play an important role in defense against pathogens. These molecules have been explored as immunotherapeutics against various cancer-associated targets. Two receptors exclusively expressed in B lymphocytes have been investigated over the years as targets for malignancy treatment: CD19 and CD20. The anti-CD20 rituximab was the first antibody approved for cancer immunotherapy. Despite its therapeutic success, some patients do not respond well to the treatment. CD19, on the other hand, has been explored in other immunotherapies, such as CAR-T cells and bispecific molecules. The phage display technique was used to explore methodologies to mature the affinity of rituximab antibody against the target and to develop new anti-CD19 antibodies, using nextgeneration sequencing techniques to propose candidates. For the CD20 target, a CD20 mimotope peptide was used, and three candidate molecules were proposed. Only one of them was successfully expressed in a bacterial system and, despite high enrichment in phage display selection, this molecule lost its binding capacity to CD20+ cells, suggesting a complex interaction with rituximab. One mutant was expressed in a eukaryotic system, and binding to CD20+ cells was observed by flow cytometry, as well as a likely cytotoxic activity against Raji cells. For the CD19 target, only two molecules were tested, showing low binding. In the future, new combinations of VH and VL chains and testing of other candidates will be conducted to obtain functional molecules. The strategy used generated candidates based solely on sequence enrichment through phage display selection steps. The molecules can also be studied in the FvFc format, containing a constant portion, to assess their effector properties.